Peran Keluarga Menanggulangi Terorisme Tinjauan Hukum Islam dalam Kursus Pra Nikah - Mufrod Teguh Mulyo; Khoiruddin Nasution; Munifah Munifah; Jumni Nelli (Universitas Wahid Hasyim Semarang, 2022)
This paper seeks to strengthen the opinion or concept that states the importance of the family in dealing with the terrorism crisis in Indonesia. This paper is the result of qualitative research on a variety of data sources (works); books and articles discussing and or researching the role of the family in dealing with terrorism emergencies. Berger's theory of social construction is used to see the role and or function of writing, where this paper is still at the level of externalization, of three steps; externalization, objectification, and internalization to become Social Actions, to become people's habits. Meanwhile, in order to control social actions, it employs preventive and repressive measures, while on the process side, it employs persuasive, coercive, and curative measures. As a result, three conclusions are possible. First, terrorism remains a social problem in Indonesia, requiring serious, substantial, and long-term solutions. Second, there are several reasons and or reasons why terrorism remains a social problem, but the core of the problem is the role and or function of the family that does not work or runs optimally. Third, in order for the family role and or function to function properly, both the husband and wife must be competent in the field of family roles and or functions. These competencies are attained by husband and wife through participation in the Pre-Marriage Course, Bride and Groom Candidate. As a result, husbands and wives to be must attend a marriage course and all of its variations at least once before marriage, and it is preferable to be present during marriage.Keywords: Role/function of family; Counter terrorism; Marriage course.Tulisan ini bertujuan menguatkan pendapat atau konsep yang menyatakan betapa penting peran keluarga dalam menanggulangi darurat terorisme di Indonesia. Tulisan ini merupakan hasil penelitian kualitatif terhadap sejumlah sumber data (karya), buku dan artikel dan atau hasil penelitian mengenai pentingnya peran keluarga dalam menanggulangi darurat terorisme. Untuk melihat peran dan atau fungsi tulisan digunakan teori konstruksi social berger, dimana tulisan ini masih berada pada level ekternalisasi, dari tiga langkah; eksternalisasi, objektivikasi dan internalisasi untuk menjadi tindakan sosial. Sementara dalam upaya pengendalian tindakan sosial dari sisi sifatnya menggunakan usaha preventif dan represif, dari sisi prosesnya menggunakan usaha persuasif, koersif dan kuratif. Hasilnya ada tiga kesimpulan yang dapat dicatat. Pertama, terorisme masih menjadi masalah sosial di Indonesia, yang membutuhkan penanganan serius, substansial dan berkelanjutan. Kedua, ada beberapa alasan dan atau penyebab mengapa terorisme masih menjadi masalah sosial, namun inti dari masalahnya adalah peran dan atau fungsi keluarga yang kurang berjalan maksimal. Ketiga, agar peran keluarga berjalan dengan baik, pasangan suami dan isteri harus mempunyai kompetensi bidang peran dan atau fungsi keluarga. Kompetensi itu didapat oleh pasangan suami dan isteri di antaranya adalah dengan mengikuti Kursus/bimbingan calon pengantin. Karena itu, mengikuti kursus perkawinan dan segala jenisnya harus diikuti calon suami dan isteri, minimal sekali sebelum perkawinan, malah akan lebih baik ada juga selama dalam perkawinan.